Mediating Role of Coping Ability between Servant Leadership Style and Burnout among Nepalese Nurses during the COVID-19 Pandemic: A Cross-sectional Study - Gautam, Prakash; Paudel, Kamala (Journal of Nursing Education of Nepal, 2023)
Background: Nurses were the frontline health professionals caring for patients during the COVID-19 pandemic. Uncertainty of life caused job stress and burnout, but the effective mobilization of health workers saved people’s lives. In this context, this study intended to examine the effect of servant leadership in predicting nurses’ burnout by employing the perspective of social exchange theory and emotional contagion theory. Aims: This study aimed to examine the mediating role of coping ability between servant leadership and job burnout among nurses in Nepal. Methods: This research employed a cross-sectional survey with a quantitative research approach. Data were collected from 389 nurses with personal contact via an online Google form using a Likert questionnaire and the snowball sampling approach. Data were analyzed based on partial least squares because of highly correlated predictors of the predicting variable, using SPSS-AMOS. Results: Servant leadership (β=- 0.25; 95%CI=0.42, 0.73) and coping ability (β=-048;CI=0.53,0.86) have an inverse relationship with nurses’ burnout. Results revealed a significant effect of coping ability in the relationship between servant leadership and job burnout. Conclusion: Servant leadership significantly reduces nurses’ burnout. It is more effective in association with the coping ability of nurses. Originality: This study stresses the application of servant leadership for effective customer care during a crisis. This study contributes to crisis management practices in mobilizing health workers about social exchange and emotional contagion theories. DOI: https://doi.org/10.62143/x65sqq24